3‐D Extracellular Matrix from Sectioned Human Tissues. Issue 1 (3rd March 2014) - Campbell, Catherine B.; Cukierman, Edna; Artym, Vira V.
Abstract: Cell adhesion, migration, and signaling in physiologically normal and pathological processes depend highly on the extracellular matrix that the cell interacts with. A variety of in vitro models of two‐dimensional and three‐dimensional extracellular matrices have been developed to study multiple aspects of cellular behavior. However, there is a profound need for in vitro models of extracellular matrices to closely mimic both biochemical and physical aspects of a three‐dimensional in vivo cellular environment. This unit outlines the preparation of human‐tissue‐derived, cell‐free, three‐dimensional extracellular matrices for studying cellular behavior and cell‐extracellular matrix interactions ex vivo. These protocols can be used to prepare cell‐free matrices from a variety of normal and cancerous tissues. This unit also provides protocols for quality control of acellular matrix preparations, and for immunostaining of cells for specific cellular proteins as well as of extracellular matrices for their components. Curr. Protoc. Cell Biol . 62:19.16.1‐19.16.20. © 2014 by John Wiley & Sons, Inc.